An Enhanced Anycast Routing Protocol: Nearest PIM-SM Extension with Loadbalancing Schemes - Sun, Liew Chee; Chaw, Ling Teck; Ting, Su Moon; Lip Yee, Por; Keong, Phang Keat (Malaysian Journal of Computer Science, 2006)
The primary issue with anycast routing protocol is the tradeoff between performance and reliability. An anycast routing protocol that can provide shorter end-to-end delay does not always has lower packet loss, and vice versa. This paper focuses on achieving short end-to-end delay and low packet loss, and proposes an enhancement to the anycast routing protocol called the nearest Protocol Independent Multicast – Sparse Mode (PIM-SM) extension. This extension supports two load-balancing schemes, i.e. shortest-path and round-robin. The UMJaNetSim network simulator is used as the simulation environment for evaluating the nearest PIM-SM extension. Other necessary protocols such as Internet Control Message Protocol Version 6 (ICMPv6) and Multicast Listener Discovery (MLD) are implemented as well. Simulation results show that the proposed mechanisms for anycast routing improve the performance by reducing end-to-end delay and packet loss ratio.